2015
DOI: 10.1080/10962247.2015.1100141
|View full text |Cite
|
Sign up to set email alerts
|

Production of sugarcane bagasse-based activated carbon for formaldehyde gas removal from potted plants exposure chamber

Abstract: Agricultural wastes such as rice straw, sugar beet, and sugarcane bagasse have become a critical environmental issue due to growing agriculture demand. This study aimed to investigate the valorization possibility of sugarcane bagasse waste for activated carbon preparation. It also aimed to fully characterize the prepared activated carbon (BET surface area) via scanning electron microscope (SEM) and in terms of surface functional groups to give a basic understanding of its structure and to study the adsorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…This proved that the prepared activated carbon is mesoporous since the methylene blue is used to characterize mesoporous activated carbons. Mohamed et al (2015a) reported that the sugarcane bagasse-based activated carbon was used successfully as adsorbing agents for the removal of MB dye (around 90%) from aqueous solutions. The isotherms of MB adsorption were evaluated according to the major two parameter models, Langmuir and Freundlich.…”
Section: Methylene Blue Adsorption Studiesmentioning
confidence: 99%
“…This proved that the prepared activated carbon is mesoporous since the methylene blue is used to characterize mesoporous activated carbons. Mohamed et al (2015a) reported that the sugarcane bagasse-based activated carbon was used successfully as adsorbing agents for the removal of MB dye (around 90%) from aqueous solutions. The isotherms of MB adsorption were evaluated according to the major two parameter models, Langmuir and Freundlich.…”
Section: Methylene Blue Adsorption Studiesmentioning
confidence: 99%
“…The detail composition are 50% cellulose, 25% lignin and 25% hemicellulose 4,6,7) . The high cellulose content is an important point to choose the bagasse for raw material carbon production [8][9][10] . Carbon-based materials are functional for many purposes such as for gas adsorption 11,12) , wastewater treatment 13) , electrodes in media storage 14,15) , antibacterial agent 16) , gas storage 17) , and for photocatalytic uses 18) .…”
Section: Introductionmentioning
confidence: 99%
“…A great variety of adsorbents (natural or synthetic) have been used for the removal of organic substances from industrial air effluents and aqueous solutions. Activated carbons are considered as the most effective organics adsorbents with high surface areas (Andriantsiferana et al, 2015;Mohamed et al, 2015;Mohamed et al, 2016aMohamed et al, , 2016b. The adsorption capacity of activated carbon for the liquid adsorption of phenolic compounds depends on the solution conditions such as temperature, pH, ionic strength; and the adsorbate concentration (Magdy et al, 2018).…”
Section: Introductionmentioning
confidence: 99%